1990
DOI: 10.1093/ajcp/93.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study on Pancreatic Secretory Trypsin Inhibitor (PSTI) in Gastric Carcinomas

Abstract: The expression of pancreatic secretory trypsin inhibitor (PSTI) was studied immunohistochemically in 106 cases of gastric carcinoma. Of the 45 intestinal-type carcinomas, 34 cases (76%) expressed PSTI: 15 (63%) of 24 early carcinomas and 19 (90%) of 21 advanced carcinomas, the incidence being significantly different (P less than 0.05). Furthermore, in the intestinal-type carcinomas, a significant correlation was observed between PSTI expression and clinical stage or nodal involvement. On the other hand, of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…Nevertheless, several investigators have recently shown that PSTI may have functions other than the inhibition of trypsin activity, such as growth factor action (Niinobu et al, 1986;Ogawa et al, 1985Ogawa et al, , 1987. In fact, we have shown that the expression of PSTI in gastric cancer may possibly be associated with tumour growth and progression (Higashiyama et al, 1990).Although it has been reported that PSTI may be expressed in villous adenoma of the colon (Bohe et al, 1986;Tomita et al, 1987), there has been-u-study of the expression of PSTI in colorectal cancer, except for the preliminary report (Ogawa et al, 1987). In the present study, we demonstrate that colorectal cancer may also express PSTI, not only by immunohistochemical analysis for detection at the product level but also by in situ hybridisation and Northern blot hybridisation for detection at the transcriptional level.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Nevertheless, several investigators have recently shown that PSTI may have functions other than the inhibition of trypsin activity, such as growth factor action (Niinobu et al, 1986;Ogawa et al, 1985Ogawa et al, , 1987. In fact, we have shown that the expression of PSTI in gastric cancer may possibly be associated with tumour growth and progression (Higashiyama et al, 1990).Although it has been reported that PSTI may be expressed in villous adenoma of the colon (Bohe et al, 1986;Tomita et al, 1987), there has been-u-study of the expression of PSTI in colorectal cancer, except for the preliminary report (Ogawa et al, 1987). In the present study, we demonstrate that colorectal cancer may also express PSTI, not only by immunohistochemical analysis for detection at the product level but also by in situ hybridisation and Northern blot hybridisation for detection at the transcriptional level.…”
mentioning
confidence: 52%
“…Nevertheless, several investigators have recently shown that PSTI may have functions other than the inhibition of trypsin activity, such as growth factor action (Niinobu et al, 1986;Ogawa et al, 1985Ogawa et al, , 1987. In fact, we have shown that the expression of PSTI in gastric cancer may possibly be associated with tumour growth and progression (Higashiyama et al, 1990).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Its role has been considered to be a specific inhibitor that prevents autoactivation of trypsinogen in the pancreas and pancreatic juice [41]. Later studies showed that PSTI was also expressed in some extrapancreatic normal tissues [39,4345] and in various cancers, including pancreatic [34], colorectal [35], gastric [36], lung [37], and hepatocellular [38] cancers. It was found that the serum concentration of immunoreactive PSTI is elevated after surgery, trauma and severe infection [45][46][47], suggesting that PSTI is an acute phase reactant.…”
Section: Controlmentioning
confidence: 99%
“…These phenomena imply that PSTI has other physiological and pathological roles in addition to the inactivation of trypsin. Several papers suggest that tumor-derived PSTI acts as autocrine or paracrine growth factor [46,[50][51][52][53][54], and is associated with the tumor growth of stromal proliferation of fibrous tissues [36,37], although it has been reported recently that the evaluation of tumor-derived PSTI as a paracrine or autocrine growth factor is not definite and needs confirmation [55]. The hPSTI mRNA expression in type II citrullinemia patients was equivalent to the level in hepatic cancer portions (Figs.…”
Section: Controlmentioning
confidence: 99%